Rare cause of gastric varices secondary to an isolated left gastric vein stenosis - Umair, Masood; Anuj, Sharma; Sonny, Nijjar; Natalie, Pavelock; Divey, Manocha (Journal of Digestive Disorders And Diagnosis, 2016)
A 69 year old female with a history of pancreatic mucinous cystadenoma (treated with Whipple procedure) and recently presumed liver cirrhosis presented to the hospital with melanotic stools. The source of the bleeding was initially thought to be secondary to upper gastrointestinal (GI) varices due to portal hypertension from the liver disease. Upper endoscopy found no active bleeding and confirmed grade 2 gastric varices with gastric wall edema. Due to persistent symptoms and inability to locate the exact source, she went to the operating room for possible transjugular intrahepatic portosystemic shunt (TIPS) but was not found to have any porto-systemic gradient. Instead, she was found to have an isolated stenosis of the left gastric vein, which was treated with balloon angioplasty and eventual splenectomy. Upper GI varices usually occur due to portal hypertension from liver disease. Extra hepatic causes are much rarer. We report a case of upper GI bleed from gastric varices secondary to left gastric vein stenosis rather than portal hypertension. The stenosis was due to a rare complication of a Whipple procedure. The case is unique as there are no reported cases of gastric varices secondary to left gastric vein stenosis.
Keywords: Left gastric vein; stenosis; varices; gastrointestinal bleed